Anti-Intellectualism and Israeli Politics. Issue 4 (1st October 2016) - Siniver, Asaf
Abstract: Anti-intellectualism is a discrete social phenomenon which eschews spatial or temporal boundaries. While it defies a restrictive definition, it is commonly understood as a populist disdain of individuals who speak of certain universal values and engage in the pursuit of knowledge from reason; conversely, an anti-intellectual is a person who is not a 'dealer in ideas' and is not committed to the 'life of the mind'. This article focuses on anti-intellectualism as a defining characteristic of the Israeli ethos which predates the establishment of the Jewish state. The article begins with a terminological discussion and a brief historical survey of the prevalence of anti-intellectualism in contemporary societies. It then traces the roots of Israeli anti-intellectualism and examines their manifestations in the case of Abba Eban, Israel's most quintessential diplomat, an orientalist scholar, a Cambridge don, a polyglot and a public intellectual. The article concludes by pointing to the uneasy fit between the political and intellectual spheres in Israeli politics and the challenges posed by the former to the latter.